Improving Left Atrial Appendage Occlusion Device Size Determination by Three-Dimensional Printing-Based Preprocedural Simulation - Kim, William D.; Cho, Iksung; Kim, Young Doo; Cha, Min Jae; Kim, Sang-Wook; Choi, Young; Shin, Seung Yong (Frontiers in Cardiovascular Medicine, 2022)
Background: Two-dimensional-based left atrial appendage (LAA) occluder (LAAO) size determination using transesophageal echocardiography (TEE) is limited by the structural complexity and wide anatomical variation of the LAA. Objectives: This study aimed to assess the accuracy of LAAO size determination by implantation simulation using a three-dimensional (3D) printed model compared with the conventional method based on TEE. Methods: We retrospectively reviewed patients with anatomically and physiologically properly implanted Amplatzer Cardiac Plug and Amulet LAAO devices between January 2014 to December 2018, using the final size of the implanted devices as a standard for size prediction accuracy. The use of 3D-printed model simulations in device sizing was compared with the conventional TEE-based method. Results: A total of 28 cases with percutaneous LAA occlusion were reviewed. There was a minimal difference (-0.11mm; 95% CI [-0.93, 0.72mm]; P=0.359) between CT-based reconstructed 3D images and 3D-printed LA models. Device size prediction based on TEE measurements showed poor agreement (32.1%), with a mean difference of 2.3±3.2 mm (95% CI [-4.4, 9.0]). LAAO sizing by implantation simulation with 3D-printed models showed excellent correlation with the actually implanted LAAO size (r=0.927; bias=0.7±2.5). The agreement between the 3D-printed and the implanted size was 67.9%, with a mean difference of 0.6 mm (95% CI [-1.9, 3.2]). Conclusions: The use of 3D-printed LA models in LAAO size determination showed improvement in comparison with conventional 2D TEE method.